Mobile Augmented Reality for Flood Visualisation. (November 2018) - Haynes, Paul; Hehl-Lange, Sigrid; Lange, Eckart
Abstract: Mobile Augmented Reality (MAR) for environmental planning and design has hardly been touched upon, yet mobile smart devices are now capable of complex, interactive, and immersive real time visualisations. We present a real time immersive prototype MAR app for on site content authoring and flood visualisation combining available technologies to reduce implementation complexity. Networked access to live sensor readings provides rich real time annotations. Our main goal was to develop a novel MAR app to complement existing flood risk management (FRM) tools and to understand how it is judged by water experts. We present app development in context of the literature and conduct a small user study. Going beyond the presented work, the flexibility of the app permits a broad range of applications in planning, design and environmental management. Graphical abstract: Image 1 Highlights: We present a prototype browsing and authoring tool for in-situ flood visualisation. The system is linked to the WeSenseIt sensor array, for live sensor readings. Our evaluation shows positive stakeholder feedback, suggesting the tool has potential in flood risk management domain.